The girl from home : a novel - Mitzner, Adam (Gallery Books, 2016)
"The acclaimed author, whose recent novel of suspense Losing Faith was declared "startling ... a well-crafted story" (Kirkus Reviews), takes you on a gripping psychological thrill ride in this electrifying tale of a millionaire who will go to deadly lengths to get what he wants. Jonathan Caine is a true master of the universe--a currency wizard with a trophy wife, a penthouse condo with a view of the Statue of Liberty, and the desire for more--when his world comes crashing down, spiraling him into a relentless fall from grace. Devastated, Jonathan returns to his hometown to care for his ailing father and attend his twenty-fifth high school reunion, where he becomes reacquainted with former prom queen Jacqueline Williams. Back in the day, Jackie didn't even know Jonathan existed. Now she is intrigued by the man he has become. But their budding relationship has problems, not the least of which is Jackie's jealous and abusive husband. Jonathan is determined to learn from his mistakes, but is he capable of complete transformation? Or will a shocking temptation test his desire for redemption beyond anything he could have imagined?"--